Exploring Impulsive Buying and Sustainability in Live Commerce: A Conceptual Study on Men’s Cosmetics - Fera, Nelfianti; Usep, Suhud; Setyo Ferry, Wibowo; Christian Wiradendi, Wolor (INTI International University, 2026)
This conceptual work explores the dynamics of impulsive purchase behavior under the context of live commerce and takes special focus on men’s cosmeceutical products. The novelty of the research clings to the examination of the impulsive purchase orientations of millennial male shoppers, till today overlooked both by marketing and sustainability studies. In the urban city of Bekasi, the analysis intends to identify the drivers for live-stream impulsive purchase and their sustainable marketing-related consequences. Placing the discussion under sustainability, the paper thus highlights the way through which commercial moves can be compromised with responsible consumption interaction where consumption consciousness can be advocated and the rising utilization of the channels of live commerce can be utilized. As being a conceptual analysis, the paper avoids empirical support and instead converges available theories and models for the sake of proposing a conceptual framework where sustainable marketing strategies can be integrated with impulsive purchase behavior under the men’s cosmeceutical category. In its outcomes, the analysis intends to lay the cornerstone for future empirical studies and practical uses for organizations for the establishment of both economic and ecological sustainability